Supply Chain Management Ayam Potong Ud Budi di Desa Dauh Puri Kaja Denpasar - Yudiarini, Nyoman; Pratiwi, Luh Putu Kirana; Amaral, Ni Putu Anglila (Universitas Batangahari Jambi, 2024)
The high demand for broiler chickens has promising prospects for development. In 2023, broiler chicken production is projected to reach 5.8 million/ton/year, while chicken meat consumption is estimated to reach 7.46 kg/capita/year. Indonesia is actively trying to increase livestock productivity in an effort to meet the nutritional needs of the community. The main objective of this research is to analyze supply chain management and the level of efficiency of the broiler chicken supply chain implemented by UD Budi. The research methodology includes descriptive analysis and examination of marketing efficiency. Research findings reveal that broiler chicken supply chain management has three streams. The product flow moves downstream, starting from the supplier at the slaughterhouse and ending with the final consumer of the chicken. On the other hand, financial flows move upstream, namely flowing from consumers back to producers (RPH). The flow of information is reciprocal and occurs in each link of the chain. Among the various marketing channels, the level I marketing channel (Producer (Slaughterhouse) – Wholesaler (UD Budi) – Consumer) shows the highest efficiency, with an efficiency value of 3.13%. Keywords: Broiler Chickens, Marketing Efficiency, Supply Chain